Enhanced cerebral oxygenation during mental and physical activity in older adults is unaltered by amnestic mild cognitive impairment - Elbanna, Stephanie; Cortez, Christopher; Smith, Elaina; Rattanavong, Jewelia; Ross, Sarah; Kline, Geoffrey; Wiechmann, April; Dyson, Hannah; Mallet, Robert T.; Shi, Xiangrong (Frontiers in Physiology, 2025)
BackgroundThe impact of amnestic mild cognitive impairment (aMCI) on cerebral oxygenation and cardiovascular responses to mental and physical challenges in elderly adults is unclear. This study compared the responses to mental (serial sevens test) and physical (isometric handgrip) challenges in older adults with vs. without aMCI.MethodsThirty-one aMCI (71.5 ± 1.1 years old) and 30 cognitively normal (70.8 ± 1.1 years old) adults participated in the study. Heart rate (HR), mean arterial pressure (MAP), systemic arterial oxygen saturation (SaO2), prefrontal cortical oxyhemoglobin (O2Hb) and deoxyhemoglobin (HHb) contents, and tissue oxygen saturation (ScO2) were continuously monitored during 2-min serial sevens mental arithmetic test and 1-min isometric handgrip at 30% of maximal voluntary contraction. Test results in the aMCI vs. non-MCI subjects were compared by two-factor ANOVA.ResultsCardiovascular and tissue oxygenation responses to testing were similar in the two groups. Although MAP increased similarly during the mental and physical challenges, increases in HR (P = 0.020), SaO2 (P < 0.001), ScO2 (P = 0.001) and O2Hb (P = 0.022) were greater during the mental vs. physical challenges in both aMCI and cognitively normal subjects.ConclusionThe mental arithmetic challenge increased the metabolic demand of the prefrontal cortex to a greater extent than the physical task. Cerebral O2 content increased more appreciably during the mental vs. physical challenges, in parallel with greater increases in HR. However, aMCI did not alter these physiological responses to mental or physical challenges.